Interdisciplinary Nature of Information Science and Technology (IST):A Quantitative Analysis - Gopinath, M. A.; Patil, M. D. (Journal of Information and Knowledge, 1991)
This is a study of the literature published in the field of Information Science and Technology(IST). It identifies different types of bonding, such as, borrows, clustering, fusion and other associations. The study uses the review articles published in the Annual Review of Information Science and Technology during 1985-89. It analyses the term-concept relations in the summarized topics of the texts. The rate of incidence of the different disciplines associated with IST are studied. The quantitative analysis indicates that the transaction concepts to IST are provided by the fields of Computer Technology, Telecommunication Technology, Information Storage Technolgy and Artificial Intelligence. The fields in which information is utilized are indicated as Business, Commerce, Law, Medicine, Engineering, Chemical Technology, and Agriculture. Humanities and Social Sciences have been providing the theoretical base for human transactions in information science.